Simulation of the penetration range distribution for low energy ions injected into plant seeds - Linxiang, Wang (Bangladesh Journal of Botany, 2018)
In the present experiment on low-energy ions implanted into seeds, factors such as the unique microstructure of the seeds, the energy and injection mode of the ions, the step diameter and scattering angle of the ions after collision, and the collision energy loss between ions and atomic nuclei or electrons are considered. A modified model for ions implanted into seeds is established. The range distribution is simulated for vanadium, titanium, and iron ions (V+, Ti+, and Fe+) with different energies and injection modes implanted into peanut, cotton, and wheat seeds, using the FORTRAN programming language and Monte-Carlo method; the results are in good agreement with the experimental data. In addition, the model is used to estimate the range distribution for nitrogen, hydrogen, and argon ions (N+, H+, Ar+) implanted into peanut, cotton and wheat seeds.